EKSPLORASI LOYALITAS PELANGGAN PADA KEPESERTAAN BPU DI BPJS KETENAGAKERJAAN: DAMPAK CONTINUANCE INTENTION DAN PEMBAYARAN DIGITAL - Nandika, I Gusti Ngurah Agung Gde Putra; Sanica, I Gede; Adhiya Garini Putri, Dewa Ayu Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.11.TAHUN.2024, 2024)
This study investigates the mediating effect of customer loyalty on the relationships between digital payment methods, customer experience, transaction security, and continuance intention in the context of membership fee payments at a BPJamsostek branch in Denpasar, Bali. Employing Structural Equation Modeling (SEM) with Partial Least Squares (PLS), the research examines three independent variables: digital payment methods, customer experience, and transaction security. Customer loyalty serves as the mediating variable, with continuance intention being the dependent variable. The analysis reveals a significant positive impact of digital payment methods on both continuance intention (the intention to continue using the service) and customer loyalty. However, customer experience exhibits a positive but non-significant influence on these factors. Conversely, transaction security demonstrates a significant positive influence on both continuance intention and customer loyalty. Interestingly, customer loyalty does not mediate the relationship between customer experience and continuance intention. In contrast, transaction security mediates its influence on continuance intention within the membership fee payment scheme. Future research could extend this work by exploring different independent variables or incorporating additional factors, such as user satisfaction or expectations, into the model.